Assessment of general characteristics of patients with primary metastatic breast carcinoma: single center experience - Uyeturk, Ummugul; Budakoglu, Burcin; Turker, İbrahim; Helvaci, Kaan; Sonmez, Ozlem Uysal; Aktas, Gulali; Arslan, Ulku Yalcintas; Oksuzoglu, Omur Berna Cakmak (Contemporary Oncology/Współczesna Onkologia, 2013)
Introduction: Breast cancer (BC) is a heterogeneous disease. Several subgroups have been identified, according to the clinical presentation and radiographic, pathological, biological, and molecular characteristics of the tumor. Intrinsic genetic heterogeneity may be responsible for these differences. To date, little is known about the clinical features and outcome of patients with primary metastatic BC (PMBC) defined as those presenting with stage IV disease. Material and methods: Between September 2007 and May 2011, BC patients who were admitted to a clinic were assessed. Patients with PMBC were included in this retrospective analysis. The patients’ demographic characteristics, treatment schedules, and survival data were recorded. Results : Of 2478 BC patients, 102 (4.1%) with PMBC were included in the analysis. The median age of the patients was 50 (26–90) years. Only four patients (3.9%) had previously undergone mammography. The median progression-free survival (PFS) and overall survival (OS) were 30 and 66 months, respectively. The PFS and OS were unaffected by age, menopausal status, ECOG, histology, or tumor grade. Both PFS and OS were affected by HR status (log rank p = 0.006, log rank p = 0.04), HER2 status (p = 0.001, p = 0.005), site of metastasis (p = 0.01, p = 0.04), radiotherapy (p = 0.04, OS p = 0.03), and bisphosphonate treatment (p = 0.02, p = 0.006). PFS was greater in the hormone therapy group (43 months, p = 0.03) while OS was greater in the patients that received chemotherapy (76 months, p = 0.01). Conclusions : Mammography should be given greater emphasis, considering its importance in the prevention of PMBC. As a treatment option for bone and soft tissue metastatic PMBC patients, hormone therapy should be effective as a first-line treatment.